A Systematic Review and Meta-Analysis of Lipid Signatures in Post-traumatic Stress Disorder - Bharti, Veni; Bhardwaj, Aseem; Elias, David A.; Metcalfe, Arron W. S.; Kim, Jong Sung (Frontiers in Psychiatry, 2022)
Background: Research assessing lipid levels in individuals diagnosed with posttraumatic stress disorder (PTSD) has yielded mixed results. This study aimed to employ meta-analytic techniques to characterize the relationship between the levels of lipid profiles and PTSD. Methods: We performed meta-analyses of studies comparing profiles and levels of lipids between PTSD patients and healthy individuals by searching Embase, Ovid Medline, Scopus, PsycINFO, and Cochrane databases for the studies until March 2021. Meta-analyses were performed using random-effects models with the restricted maximum-likelihood estimator to synthesize the effect size assessed by standardized mean difference (SMD) across studies. Findings: 8657 abstracts were identified, and 17 studies were included. Levels of total cholesterol (TC) (SMD=0.57 95% CI 0.27 to 0.87, p=0.003), low-density lipoprotein (LDL) (SMD=0.48, 95% CI=0.19 to 0.76, p=0.004), and triglyceride (TG) (SMD= 0.46, 95% CI 0.22 to 0.70, p=0.001) were found to be higher, while levels of high-density lipoprotein (HDL) (SMD=-0.47, -0.88 to -0.07, p=0.026) were found to be lower in PTSD patients compared to healthy controls. Subgroup analysis showed that TG levels were higher in PTSD patients who were on or off of psychotropic medications, both <40 and ≥40 years of age, and having body mass index of <30 and ≥30 compared to healthy controls. Interpretation: This work suggested dysregulation of lipids in PTSD that may serve as biomarker to predict the risk. The study will be useful for physicians considering lipid profiles in PTSD patients to reduce cardiovascular morbidity and mortality.